Carbetocin at elective caesarean section: a sequential allocation trial to determine the minimum effective dose in obese women. (22nd December 2019) - Drew, T.; Balki, M.; Farine, D.; Ye, X. Y.; Carvalho, J. C. A.
Summary: Postpartum haemorrhage is a leading cause of maternal death during childbirth. There is an increasing incidence of atonic postpartum haemorrhage in developed countries, and maternal obesity has been proposed as a contributing factor. The dose–response relationship of carbetocin in obese women has not yet been determined. We conducted a double‐blind, dose‐finding study of carbetocin using a biased coin up‐and‐down design in women with a body mass index ≥ 40 kg.m −2 undergoing elective caesarean section. The determinant for a successful response was satisfactory uterine tone, with no intra‐operative need for additional uterotonic drugs. Secondary outcomes included the use of additional uterotonic drugs postoperatively, estimated blood loss and adverse effects of carbetocin administration. Thirty women were recruited to the study. The median (IQR [range]) body mass index was 44.93 (41.5–55.2 [40–66.5]) kg.m −2 . The ED90 of carbetocin was estimated as 62.9 (95%CI 57.0–68.7) μg using the truncated Dixon and Mood method, and 68 (95%CI 52–77) μg using the isotonic regression method. The estimated blood loss was 880 (621–1178 [75–2442]) ml. The overall rates of hypotension and hypertension after delivery were 40% and 6.7%, respectively, while nausea occurred in 26.7% of women. The ED90 for carbetocin in obese women at elective caesarean section is lower than the dose of 100 μg currently recommended by the Society of Obstetricians and Gynaecologists of Canada, but is approximately four times higher than the previously demonstrated ED90 of 14.8 μg in women with body mass index < 40 kg.m −2 .